Unusual charge configurations in transcription factors of the basic RNA polymerase II initiation complex. - Karlin, S (1993)
A systematic analysis of the primary sequences of the polymerase II initiation complex has revealed unusual charge features in the TFII family proteins. In particular, the proteins TFIIA alpha, TFIIE alpha, and TFIIF carry multiple charge clusters and hyper charge runs, sequence features occurring in < 4% of all (available) eukaryotic proteins. Possible implications for these charge structures are discussed in relation to the assembly and function of the polymerase II transcriptional complex.